Spiders hanging out in the rain - Barrantes Montero, Gilbert (2021)
Behavioural adjustments to changing environmental conditions are advantageous for spiders, as such adjustments likely allow spiders to remain in good hunting sites. Here, we describe the behavioural response of seven araneoid species to heavy rain in the neotropics. Five of the seven spiders drastically modified their position on the web, relative to the typical resting position. Four of these species (Allocyclosa bifurca, Argiope argentata, Cyrtophora citricola, and Leucauge mariana) hung from hub threads using their legs III and IV, oriented the anterior section of the prosoma downward, and moved legs I and II forward in front of the spider's eyes. Trichonephila clavipes had a similar response, but hung from only its legs IV. Two other species (Gasteracantha cancriformis and Micrathena duodecimspinosa) did not show an apparent response to heavy rain. The change in position reduces the spider's surface that heavy rain could impact, and speeds water drainage which may reduce pathogen infection.